Penerapan Model Pembelajaran Visual untuk Meningkatkan Hasil Belajar IPS Siswa MI Tarbiyatul Islam - Listrianti, Feriska; Ratnasari, Ratnasari; Fatmawati, Sulis (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2022)
From the results of direct observations carried out on March 6, 2022, it was found that the teacher still taught students only by using the lecture, question and answer, and assignment methods. Then the learning environment that only takes place in the classroom makes learning boring. These methods tend to make students unable to make connections between what is learned and how that knowledge is used. This can be seen from the learning outcomes of social studies subject matter that need to be improved. To improve social studies learning outcomes through the application of visual learning models to students of class V A even Semester at MI Tarbiyatul Islam. This study aims to improve social studies learning outcomes through the application of visual media-assisted contextual learning models for even semester V A grade students at MI Tarbiyatul Islam Kandang Jati Kulon in the 2021/2022 academic year. This research is classroom action research which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The research subjects were students of class V A MI Tarbiyatul Islam Kandang Jati Kulon totaling 35 students consisting of 12 male students and 23 female students. Data collection in this study was carried out by the test method. The data collected were analyzed by descriptive statistical analysis and quantitative descriptive analysis. The results showed that the average social studies learning outcomes in the first cycle was 75.45 in the medium category and in the second cycle increased to 87.23 in the high category. The increase that occurs if it is calculated using the Gn formula, the score score is 0.48 which if converted to the criteria table for improving learning outcomes is in the medium category. Thus, it can be concluded that the application of the contextual learning model assisted by visual media can improve social studies learning outcomes for class V A MI Tarbiyatul Islam Kandang Jati Kulon academic year 2021/2022